First report on the association of drinking water hardness and endothelial function in children and adolescents - Poursafa, Parinaz (Termedia Publishing House, 2014)
INTRODUCTION: This study aims to investigate the relationship of water hardness and its calcium and magnesium content with endothelial function in a population-based sample of healthy children and adolescents. MATERIAL AND METHODS: This case-control study was conducted in 2012 among 90 individuals living in two areas with moderate and high water hardness in Isfahan County, Iran. The flow-mediated dilatation (FMD) of the brachial artery and the serum levels of soluble adhesion molecules (sICAM-1, sVCAM-1) were measured as surrogate markers of endothelial function, and high-sensitivity C-reactive protein (hs-CRP), as a marker of inflammation. RESULTS: Data of 89 participants (51% boys, mean age 14.75 (2.9) years) were complete. Those participants living in the area with high water hardness had higher FMD, hs-CRP, and soluble adhesion molecules (sICAM-1, sVCAM-1) than their counterparts living in the area with moderate water hardness. Multiple linear regression analysis showed that after adjustment for confounding factors of age, gender, body mass index, healthy eating index and physical activity level, total water hardness, as well as water content of calcium and magnesium, had a significant positive relationship with FMD. The corresponding associations were inverse and significant with soluble adhesion molecules (p < 0.05). CONCLUSIONS: This study, which to the best of our knowledge is the first of its kind in the pediatric age group, suggests that water hardness, as well as its calcium and magnesium content, may have a protective role against early stages of atherosclerosis in children and adolescents.